Asking the right questions about electronic voting - Celeste, Richard F.; Thornburgh, Dick; Lin, Herbert (National Academies Press, 2006)
Many election officials look to electronic voting systems as a means for improving their ability to more effectively conduct and administer elections. At the same time, many information technologists and activists have raised important concerns regarding the security of such systems. Policy makers are caught in the midst of a controversy with both political and technological overtones. The public debate about electronic voting is characterized by a great deal of emotion and rhetoric. Asking the Right Questions About Electronic Voting describes the important questions and issues that election officials, policy makers, and informed citizens should ask about the use of computers and information technology in the electoral process--focusing the debate on technical and policy issues that need resolving. The report finds that while electronic voting systems have improved, federal and state governments have not made the commitment necessary for e-voting to be widely used in future elections. More funding, research, and public education are required if e-voting is to become viable.